Subchronic toxicity of a drug based on D-cyphenothrin, pyriproxyfen and piperonyl butoxide - M. V. Arisov; D. S. Poselov; E. V. Poselova; A. A. Stepanov; T. S. Novik (Российский паразитологический журнал, 2024)
The purpose of the research is to study the effects of a combined drug based on D-cyphenothrin, pyriproxyfen and piperonyl butoxide on the body of rats with repeated dermal application in a subchronic experiment.Materials and methods. The drug subchronic toxicity was studied in the vivarium of the VNIIP – FSC VIEV on 30 male rats divided into one control and two experimental groups of 10 animals each. The drug was applied daily for 7 days to the experimental rats at doses of 1/10 and 1/20 of the maximum possible dose for dermal application determined in an acute experiment when studying LD50. On the first day and at 10 days after the last application of the drug, half of the animals from each group were euthanized and blood samples were taken to determine morphological and biochemical parameters. A macroscopic examination of the organs was carried out; their mass was determined, and mass coefficients were calculated.Results and discussion. The drug based on D-cyphenothrin, pyriproxyfen and piperonyl butoxide applied dermally for 7 days in doses of 1/10 of LD50 (3071 mg/kg) and 1/20 of LD50 (1535.5 mg/kg) had no negative effect on the rats' organism, or its physiological state, and caused no changes in the morphological or biochemical blood parameters, as well as the mass coefficients of the internal organs. Doses of 3071 and 1535.5 mg/kg were inactive (safe). The threshold and toxic doses could not be determined